1981
DOI: 10.1002/mpo.2950090504
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography brain scans in long term survivors of childhood acute lymphoblastic leukemia

Abstract: There have been varying frequencies cited for the occurrence of abnormal brain CT scans in leukemic patients and conflicting evidence about the significance of these abnormalities and their relationship to sanctuary therapy. Our study of CT brain scans in 26 long survivors of acute lymphoblastic leukemia showed an overall prevalence of 35% abnormal scans. There was no statistically significant difference between the number of abnormal scans in patients given radiotherapy as part of their CNS prophylaxis and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…However, all calcifications were detected in group B and C (4/31 [12.9%]), whereas no calcification was seen in group A (Table II). One reason for this low incidence of calcifications could be the relatively low dose of irradiation used (12)(13)(14)(15)(16)(17)(18). However, it is significant that three of four patients belonged to group B (P ‫ס‬ 0.027), i.e., the group with the ITMTX dosages before CI but with the highest cumulative dose in ITMTX and the highest number of dosages.…”
Section: Mineralizing Microangiopathymentioning
confidence: 99%
See 1 more Smart Citation
“…However, all calcifications were detected in group B and C (4/31 [12.9%]), whereas no calcification was seen in group A (Table II). One reason for this low incidence of calcifications could be the relatively low dose of irradiation used (12)(13)(14)(15)(16)(17)(18). However, it is significant that three of four patients belonged to group B (P ‫ס‬ 0.027), i.e., the group with the ITMTX dosages before CI but with the highest cumulative dose in ITMTX and the highest number of dosages.…”
Section: Mineralizing Microangiopathymentioning
confidence: 99%
“…Irradiated patients presented more frequent focal white matter necrosis, brain atrophy, calcifications and grey matter changes in radiological examinations. On the other hand, there are studies which report no significant differences between the irradiated and nonirradiated patients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The most frequent findings are white matter changes, 6,8,9,11,12,16,18,20 widening of the ventricles and/or sulci, 10,11,15,17,19,20 and cerebral calcifications. 12,14 Reduced prefrontal cortex, cerebellum, and cortical white matter volumes have also been reported.…”
mentioning
confidence: 99%
“…However, Esseltine et al (1981) found no differences in the frequency of abnormal computed tomography brain scans between children receiving cranial radiotherapy and those receiving only intrathecal methotrexate. Distractibility and memory deficits have been reported in children with ALL who received cranial irradiation when less than 8 years old (Goff et al, 1980).…”
Section: Sequelaementioning
confidence: 66%